2012
DOI: 10.1186/1756-0500-5-628
|View full text |Cite
|
Sign up to set email alerts
|

Recent incidence of type 1 diabetes mellitus in children 0–14 years in Newfoundland and Labrador, Canada climbs to over 45/100,000: a retrospective time trend study

Abstract: BackgroundTo study and update the provincial incidence of type 1 diabetes mellitus (T1DM) in Newfoundland and Labrador (NL), a province of Canada with a very high incidence previously reported in 2006, and one of the highest incidences reported worldwide. This is a retrospective time trend study of the incidence of T1DM, in children aged 0–14 years from 1987–2010 inclusive.FindingsOver the study period 931 children aged 0–14 years were diagnosed with T1DM. The incidence of T1DM in this population over the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
2
30
0
4
Order By: Relevance
“…The incidence of type 1 diabetes increased at a rate of 3.8% per year over the same period. This is consistent with average worldwide increase in the incidence of type 1 diabetes of around 3–5% . While type 2 diabetes is no longer a rare disease in youth, particularly in those from an Indigenous background, type 1 diabetes continues to represent the majority of new diabetes cases in 10–18 yr olds in our population.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of type 1 diabetes increased at a rate of 3.8% per year over the same period. This is consistent with average worldwide increase in the incidence of type 1 diabetes of around 3–5% . While type 2 diabetes is no longer a rare disease in youth, particularly in those from an Indigenous background, type 1 diabetes continues to represent the majority of new diabetes cases in 10–18 yr olds in our population.…”
Section: Discussionsupporting
confidence: 89%
“…This is in accordance with other studies reporting the increasing incidence of T1DM mostly in younger age group [11][12][13][14] , but is completely different from data reported in Croatia where the increase in the disease incidence ceased in the youngest children 15 . Similar to some other studies 16,17 , we found a steep increase in the incidence T1DM in Montenegro boys under five years of age. A slight predominance of male children is noted in the populations with a higher incidence of T1DM.…”
Section: Discussionsupporting
confidence: 80%
“…The worldwide DIAMOND Project [4] and the EURODIAB [2] multicentre prospective registration study in Europe showed an accelerating epidemic of type 1 diabetes across ethnicities and geographic areas. This trend in different countries and among different ethnicities may be explained by genetic background, chemical exposure and/or infectious pathogens among persons with diverse demographic characteristics [35]. Genetic factors alone cannot explain this rise in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%